MiR‐22 and miR‐214 targeting BCL9L inhibit proliferation, metastasis, and epithelial‐mesenchymal transition by down‐regulating Wnt signaling in colon cancer. Issue 4 (30th January 2019) - Sun, Ruifang; Liu, Zhigang; Han, Lin; Yang, Yang; Wu, Fei; Jiang, Qiuyu; Zhang, Huahua; Ma, Ruili; Miao, Jiyu; He, Kang; Wang, Xiaofei; Zhou, Dangxia; et al.
ABSTRACT: The epithelial‐mesenchymal transition (EMT) is crucial for cancer progression. Evidence has shown that miR‐22 and miR‐214 play a key role in colon cancer progression; however, the underlying mechanism remains to be known. The effects of miR‐22 and miR‐214 on EMT are contradictory in different cancers, and whether miR‐22 and miR‐214 are involved in the colon cancer EMT process needs to be elucidated. In this study, we evaluated the exact role and the regulation mechanism of miR‐22 and miR‐214 in colon cancer. After transfection with miR‐22 expression vector, the cell proliferation and migration capacity of HCT116 and RKO cells were significantly suppressed. Also, E‐cadherin was increased and vimentin was decreased by miR‐22 overexpression. Similar effects were also observed after miR‐214 expression vector transfection. Dual‐lucif erase reporter confirmed that BCL9L is the target gene of both miR‐22 and miR‐214. Silencing of BCL9L inhibits cell proliferation and migration, and the expression of E‐cadherin and vimentin was also altered by BCL9L knockdown, which was consistent with miR‐22 or miR‐214 transfection. Furthermore, miR‐22 and miR‐214 inhibited tumor growth in nude mice. Moreover, although the association between BCL9L's lower expression and longer survival time was statistically nonsignificant, a trend existed; further studies in a larger cohort are needed. Collectively, these data suggest that miR‐22 and miR‐214 inhibit cell proliferation, migration, and EMT of colon cancer, most likely by targeting BCL9L.—Sun, R., Liu, Z., Han, L., Yang, Y., Wu, F., Jiang, Q., Zhang, H., Ma, R., Miao, J., He, K., Wang, X., Zhou, D., Huang, C. miR‐22 and miR‐214 targeting BCL9L inhibit proliferation, metastasis, and epithelial‐mesenchymal transition by down‐regulating Wnt signliang in colon cancer. FASEB J. 33, 5411–5424 (2019). www.fasebj.org